Interplay between tRNA modifications and processing - Peschek, Jirka; Tuorto, Francesca (Journal of molecular biology, 2025)
Transfer RNAs play a key role during protein synthesis by decoding genetic information at the translating ribosome. During their biosynthesis, tRNA molecules undergo numerous processing steps. Moreover, tRNAs represent the RNA class that carries the largest variety and highest relative number of chemical modifications. While our functional and mechanistic understanding of these processes is primarily based on studies in yeast, the findings on dynamic tRNA maturation can be translated to higher eukaryotes including humans, particularly regarding the biochemical characterization of the multitude of enzymes involved. In this review, we summarize current knowledge on the sequential hierarchy and interplay of various processing and modification steps for mitochondrial and cytoplasmic tRNA, as well as tRNA-like structures in eukaryotic cells. We also highlight recent structural advances that shed light on the function of enzyme-tRNA complexes.
Online verfügbar: 22. Mai 2025, Artikelversion: 10 Juni 2025
Gesehen am 19.08.2025